Generation and characterization of induced pluripotent stem cells of small apes - Yusuke Hamazaki; Hiroto Akuta; Hikaru Suzuki; Hideyuki Tanabe; Kenji Ichiyanagi; Takuya Imamura; Masanori Imamura; Masanori Imamura; Masanori Imamura (Frontiers in Cell and Developmental Biology)
Small apes (family Hylobatidae), encompassing gibbons and siamangs, occupy a pivotal evolutionary position within the hominoid lineage, bridging the gap between great apes and catarrhine monkeys. Although they possess distinctive genomic and phenotypic features—such as rapid chromosomal rearrangements and adaptations for brachiation—functional genomic studies on small apes have been hindered by the limited availability of biological samples and developmental models. Here, we address this gap by successfully reprogramming primary skin fibroblasts from three small ape species: lar gibbons (Hylobates lar), Abbott’s gray gibbons (Hylobates abbotti), and siamangs (Symphalangus syndactylus). Using Sendai virus-based stealth RNA vectors, we generated 31 reprogrammed cell lines, five of which were developed into transgene-free induced pluripotent stem cells. These iPSCs displayed canonical features of primed pluripotency, both morphologically and molecularly, consistent with other primate iPSCs. Directed differentiation experiments confirmed the capacity of the small ape iPSCs to generate cells representing all three germ layers. In particular, their successful differentiation into limb bud mesoderm cells underscores their utility in investigating the molecular and developmental mechanisms unique to small ape forelimb evolution. Transcriptomic profiling of small ape iPSCs revealed significant upregulation of pluripotency-associated genes, alongside elevated expression of transposable elements. Remarkably, LAVA retrotransposons—a class of elements specific to small apes—exhibited particularly high expression levels in these cells. Comparative transcriptomic analyses with iPSCs from humans, great apes, and macaques identified evolutionary trends and clade-specific gene expression signatures. These signatures highlighted processes linked to genomic stability and cell death, providing insights into small ape-specific adaptations. This study positions small ape iPSCs as a transformative tool for advancing functional genomics and evolutionary developmental biology. By facilitating detailed investigations into hominoid genome evolution and phenotypic diversification, this system bridges critical gaps in comparative research, enabling deeper exploration of the genetic and cellular underpinnings of small ape-specific traits.